2000
DOI: 10.1002/jccs.200000081
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond Spectroscopic Studies of Tautomers of a Bisazo Compound in Solutions

Abstract: Spectroscopic properties of a fluorenone-based bisazo compound in different organic solvents have been investigated by means of the steady -state absorption and fluorescence spectroscopy and picosecond timeresolved absorption pump-probe spectroscopy. The spectra of the molecules have been shown to be mainly determined by the excitations localized on individual chromophores -azo fragments. Spectra of the azo-enol and hydrazone-quinone tautomeric forms were distinguished. Excited states of the two forms were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The shift of tautomeric equilibrium was observed in different azo compounds by adding acids or alkalis into solvents, or by changing temperature. Moreover, in some cases, the changes caused by heating remained even for several months [4]. It was also found that the type of solvent exerts a profound influence on the tautomerism.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…The shift of tautomeric equilibrium was observed in different azo compounds by adding acids or alkalis into solvents, or by changing temperature. Moreover, in some cases, the changes caused by heating remained even for several months [4]. It was also found that the type of solvent exerts a profound influence on the tautomerism.…”
Section: Introductionmentioning
confidence: 96%
“…These classes of organic compounds have extensively been used in both industry for applications such as textiles, papers, leathers, gasoline, additives, foodstuffs, cosmetics and theoretical point of view [1e3]. In addition to other applications, azo compounds are used as photosensitive species in photographic or electrophotographic systems and are the dominant organic photoconductive materials in commercial copiers [4]. Photodynamic therapy (PDT) is a new type of treatment for tumors and certain diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are used in various fields such as paper printing, electronic photography, color formers, dyeing, bleaching, polymers, liquid crystal displays, laser technology, data storage and solar energy conversion [1][2][3][4][5][6][7][8][9][10]. Recently, there is a rapidly growing interest in the potential of their biological-medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In addition to these applications, azo compounds are used as photosensitive species in photographic or electrophotographic systems and are the dominant organic photoconductive materials in commercial copiers. 8 To the best of our knowledge 2-methyl-7-phenylpyrimido [1,2-b] [1,2,4]triazepine-4,9(3H,5H)-dione (3) has not been reported hitherto. In continuation of our previous studies, we report here on the coupling of the novel ring system 3 with diazonium salts in an attempt to synthesise the respective azo derivatives 4 (Scheme 1) and the elucidation of their tautomeric structures.…”
mentioning
confidence: 99%